2015
DOI: 10.1177/0954411915585864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty infiltration in human livers on the backscattered statistics of ultrasound imaging

Abstract: Ultrasound imaging has been widely applied to screen fatty liver disease. Fatty liver disease is a condition where large vacuoles of triglyceride fat accumulate in liver cells, thereby altering the arrangement of scatterers and the corresponding backscattered statistics. In this study, we used ultrasound Nakagami imaging to explore the effects of fatty infiltration in human livers on the statistical distribution of backscattered signals. A total of 107 patients volunteered to participate in the experiments. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…In the previous study [28], some basic criteria were suggested to select the region of interest (ROI) for liver image analysis: (i) using a relatively small ROI to locate on the liver parenchyma. A small ROI easily excludes blood vessels (e.g., portal venous branches or hepatic veins) to reduce the bias of analyzing liver parenchyma; (ii) the location of the ROI should be at the focal zone, reducing the effects of attenuation and diffraction on the image analysis; (iii) selecting one ROI in individual images obtained from multiple scans of liver for averaging the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous study [28], some basic criteria were suggested to select the region of interest (ROI) for liver image analysis: (i) using a relatively small ROI to locate on the liver parenchyma. A small ROI easily excludes blood vessels (e.g., portal venous branches or hepatic veins) to reduce the bias of analyzing liver parenchyma; (ii) the location of the ROI should be at the focal zone, reducing the effects of attenuation and diffraction on the image analysis; (iii) selecting one ROI in individual images obtained from multiple scans of liver for averaging the results.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the same clinical database was established to explore the performances of Nakagami [28] and kurtosis [49] parametric imaging in staging fatty liver. The Nakagami parameter correlated with the degree of fatty liver (r obtained from curve fitting = 0.84).…”
Section: Potential Of Entropy Imaging In Evaluating Fatty Livermentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models [19,31] and clinical studies [35] have shown that the m parameter estimated by the moment-based estimators increases with the increasing severity of hepatic steatosis. Using a rat model (n = 24), Ho et al [31] reported that ultrasound Nakagami imaging is well correlated with the amount of the total cholesterol (r = 0.86; p < 0.0001) and triglyceride (r = 0.79; p < 0.0001) in the liver tissue, respectively.…”
Section: Ultrasound Nakagami Imagingmentioning
confidence: 99%